2007
DOI: 10.1016/j.ygeno.2007.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Gene identification and evidence for expression of G protein α subunits, phospholipase C, and an inositol 1,4,5-trisphosphate receptor in Aplysia californica rhinophore

Abstract: In the marine mollusk Aplysia californica, waterborne protein pheromones that are released during egg laying act in concert to stimulate mate attraction. However, molecular information concerning the cellular receptors and signaling mechanisms that may be involved in waterborne peptide and protein pheromonal communication is lacking. As a first step toward examining whether members of the G protein family and phosphoinositide signaling pathway are present in the primary peripheral chemosensory organs (i.e., rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…Finally, Aplysia Ins(1,4,5)P 3 R cDNA encodes a 2762-residue protein with an estimated molecular mass of 315 kDa that shares a high degree of identity with invertebrate Ins(1,4,5)P 3 R homologs. Consistent with a potential role in Aplysia chemical transduction, recent observations using laser capture microdissection of rhinophore sensory epithelium followed by G protein-, PLC-or Ins(1,4,5)P 3 Rspecific RT-PCR, indicate that these mRNA are expressed in rhinophore sensory epithelium (Cummins et al, 2007).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Finally, Aplysia Ins(1,4,5)P 3 R cDNA encodes a 2762-residue protein with an estimated molecular mass of 315 kDa that shares a high degree of identity with invertebrate Ins(1,4,5)P 3 R homologs. Consistent with a potential role in Aplysia chemical transduction, recent observations using laser capture microdissection of rhinophore sensory epithelium followed by G protein-, PLC-or Ins(1,4,5)P 3 Rspecific RT-PCR, indicate that these mRNA are expressed in rhinophore sensory epithelium (Cummins et al, 2007).…”
Section: Introductionsupporting
confidence: 57%
“…For the purpose of this study, we focused on PLC as a potential secondary signaling olfactory component because of recent identification of an Aplysia californica PLC homolog (Cummins et al, 2007). Fig.…”
Section: Distribution Of Aplysia Phospholipase Cmentioning
confidence: 99%
See 2 more Smart Citations
“…7, bottom right). To directly examine a possible interaction between ApHomer and Aplysia IP 3 R, we determined the coding sequence for the initial 154 amino acids of ApIP 3 R. A cDNA for Aplysia IP 3 R has also been reported, matching the sequences we obtained (Cummins et al, 2007). The consensus sequence for Homer binding is PXXFr (Tu et al, 1998), and in rat IP 3 R is found at amino acid positions 49–54.…”
Section: Resultsmentioning
confidence: 99%